George Keats of Kentucky : a life - Crutcher, Lawrence M. (Topics in Kentucky history., 2012)
John Keats's biographers have rarely been fair to George Keats (1797--1841) -- pushing him to the background as the younger brother, painting him as a prodigal son, or labeling him as the "business brother." Some have even condemned him as a heartless villain who took more than his fair share of an inheritance and abandoned the ailing poet to pursue his own interests. In this authoritative biography, author Lawrence M. Crutcher demonstrates that George Keats deserves better. Crutcher traces his subject from Regency London to the American frontier, correcting the misconceptions surrounding the Keats brothers' relationship and revealing the details of George's remarkable life in Louisville, Kentucky. Brilliantly illustrated with more than ninety color photographs, this engaging book reveals how George Keats embraced new business opportunities to become an important member of the developing urban community. In addition, George Keats of Kentucky offers a rare and fascinating glimpse into nineteenth-century life, commerce, and entrepreneurship in Louisville and the Bluegrass.